PATTERN OF PATHOGENS AND THEIR SENSITIVITY ISOLATED FROM SUPERFICIAL SURGICAL SITE INFECTIONS IN A TERTIARY CARE HOSPITAL - Ali, Syed Asad; Tahir, S. M.; Memon, Abdul Sattar; Shaikh, Noshad A. (Journal of Ayub Medical College Abbottabad, 2009)
Background: Infection is an important cause of morbidity and mortality in surgical patients. Rapidly emerging nosocomial pathogens and the problem of multi-drug resistance necessitates periodic review of isolation patterns and sensitivity in surgical practice. Surgical site infections (SSI) are defined as an infections that occurs at the incision site within thirty days after surgery. Objectives of the study were to determine the pattern of pathogens involved and their antibiotic sensitivity isolated from superficial surgical site infections in a teaching hospital. Methods: This observational study was conducted for 1 year from January 2008 to December 2008 in all 4 surgical units of Liaquat University Hospital Hyderabad which caters to patients from low socioeconomic status. Pus culture and sensitivity reports were collected prospectively from hospitalised patients who developed postoperative wound infection. The patients who developed fecal/biliary/urinary fistula or operated for malignancies, and with negative cultures were excluded from the study. Analysis was carried out using SPSS 10. Results: During the study period 112 pus culture and sensitivity reports were analyzed. E. coli 68 (60.7%) was the most common organism isolated followed by Klebsiella 23 (20.5%). The least frequent organism was staph. Epidermidis 1 (0.9%). All isolates were sensitive to penicillin derivatives and carbapenem. Quinolones, Aminoglycosides and Monobactum were also showing some promise in our study. However, Cephalosporins were ineffective against most of the important isolates in our study. Conclusion: E. coli and klebsiella were the most important isolates form SSI in our study, and penicillin derivatives and carbapenem were showing 100% antibiotic sensitivity to all of the isolates. Keywords: Superficial Surgical site infections, E. coli, Klebsiella, Penicillin derivatives, carbapenem